Bimbingan Teknis Pembuatan Google Sites: (Pengabdian Masyarakat Berbasis Inklusi Sosial pada Binaan Dinas Perpustakaan dan Arsip Kota Salatiga Komunitas Wirausaha) - Hermawan, Anton; Koerniawati, Tintien; Lestari, Elizabeth Sri; Narendra, Albertoes Pramoekti (Universitas Kristen Satya Wacana Salatiga, 2023)
This community empowerment activity was carried out in the entrepreneurial community supported by the Salatiga City Library and Archives Service. Based on the results of community service activities with the theme